2014
DOI: 10.1039/c4dt00063c
|View full text |Cite
|
Sign up to set email alerts
|

A strong adsorbent for Cu2+: graphene oxide modified with triethanolamine

Abstract: A strong adsorbent TEA-GO for Cu(2+) is prepared using TEA modified GO nanosheets. FT-IR and XPS results show that epoxy groups on GO are eliminated, and simultaneously hydroxyl groups and C-N dominate the surface groups of TEA-GO. The increased equilibrium capacity of TEA-GO for a high initial concentration of Cu(2+) makes it a promising adsorbent for heavy metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…The whole spectra can be divided into 5 peaks: C-OH, C-O-C, C=O, C=O-O and C-C. On the other hand, the huge peaks of C-C and C-O-C were observed at 285.0–287.5 eV for GO-TEOA membranes. The entire spectra consists of 6 peaks of C-N for GO modified with TEOA and C-OH, C-O-C, C=O, C=O-O and C-C for GO [33]. For all GO-TEOA membranes, it was found that the ratio of C-C, C-OH and C-N increased but that of C-O-C, C=O and C=O-O decreased compared with the unmodified GO membrane.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The whole spectra can be divided into 5 peaks: C-OH, C-O-C, C=O, C=O-O and C-C. On the other hand, the huge peaks of C-C and C-O-C were observed at 285.0–287.5 eV for GO-TEOA membranes. The entire spectra consists of 6 peaks of C-N for GO modified with TEOA and C-OH, C-O-C, C=O, C=O-O and C-C for GO [33]. For all GO-TEOA membranes, it was found that the ratio of C-C, C-OH and C-N increased but that of C-O-C, C=O and C=O-O decreased compared with the unmodified GO membrane.…”
Section: Resultsmentioning
confidence: 99%
“…These Raman and XPS spectra indicate that the oxygen-containing functional groups in GO-TEOA membranes were slightly reduced. Liu G. et al, reported that TEOA has a mild reducing ability as a chemical modifier [33]. The N + groups formed by hydrolysis of TEOA are used for ring-opening reactions of epoxides, which leads to the formation of C=C bonds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Introducing GO resulted in the appearance of stretching vibration bands at 1732, 1623, and 1040 cm À1 , corresponding to C]O, C]C, and C-O-C groups. 18,[38][39][40] These functional groups are present in GO. 36 The adsorption of adsorbates onto GO-PDMS is expected to proceed via chelation The contact time is a key parameter affecting whether heavy metal sorption reaches equilibrium.…”
Section: Morphology and Surface Characteristics Of The Go-pdms Spongementioning
confidence: 99%